2019
DOI: 10.1002/smll.201902376
|View full text |Cite
|
Sign up to set email alerts
|

Goosebumps‐Inspired Microgel Patterns with Switchable Adhesion and Friction

Abstract: directly links to the underlying mechanism of skin deformation and implies a useful function. Goosebumps represent an array of tiny bumps generated from a smooth surface through the contraction of miniature muscles that are attached to each hair, and cause the surrounding area to protrude to form bumped structures. The occurrence of goosebumps helps to regulate body temperature and takes part in heat transfer balance, but also delivers important emotional information by altering touch adhesion and friction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…However, microgels possess unique properties of both hydrogels and colloidal particles, such as structural integrity, compartmentalization, orthogonal functionalization, softness, deformability, permeability, stimuli-responsiveness, reversible swelling, and adaptivity, and have been found to be promising for a wide range of applications in various fields including controlled drug release, separation technology, bio-, and chemical sensors, etc. [312][313][314][315][316][317][318][319][320][321][322][323][324][325][326] Microgels can be fabricated mainly via emulsion polymerization with an added surfactant, surfactant-free emulsion polymerization (SFEP), inverse mini-, and microemulsion polymerization, as well as the crosslinking of prepolymer chains, etc. [327,328] Typically, the techniques used to break-up and gel the particles for microgel formation will determine the final microgel properties, including the structure, size, and strength [329] and the presence and amount of crosslinks determine the "colloidal" or "macromolecular" character of the microgel.…”
Section: Microgelsmentioning
confidence: 99%
“…However, microgels possess unique properties of both hydrogels and colloidal particles, such as structural integrity, compartmentalization, orthogonal functionalization, softness, deformability, permeability, stimuli-responsiveness, reversible swelling, and adaptivity, and have been found to be promising for a wide range of applications in various fields including controlled drug release, separation technology, bio-, and chemical sensors, etc. [312][313][314][315][316][317][318][319][320][321][322][323][324][325][326] Microgels can be fabricated mainly via emulsion polymerization with an added surfactant, surfactant-free emulsion polymerization (SFEP), inverse mini-, and microemulsion polymerization, as well as the crosslinking of prepolymer chains, etc. [327,328] Typically, the techniques used to break-up and gel the particles for microgel formation will determine the final microgel properties, including the structure, size, and strength [329] and the presence and amount of crosslinks determine the "colloidal" or "macromolecular" character of the microgel.…”
Section: Microgelsmentioning
confidence: 99%
“…Li et al corroborated these findings using poly(NIPAm-co-acrylic acid) (P(NIPAm-co-AA) microgels bound to silicon wafers, showing that microgels switched reversibly between tall conical structures in the contracted state (i.e., above 37 °C) and hemispherical structures in the swollen state (i.e., below 25 °C). [80] Silicon wafers also exhibit the innate ability to adsorb a wide array of hydrophilic polymers, such as polyethylene imine (PEI) and poly(diallyldimethylammonium chloride) (PDADMAC), which provide a route to study the effects of electrostatic interactions on microgel adsorption. For example, Schmidt et al utilized AFM and ellipsometry to examine the impact of the charge on the packing density of microgels deposited on PEI-coated silicon wafers at different pH values.…”
Section: Silica and Silicone Substratesmentioning
confidence: 99%
“…morphologies. [80] The timescale of the coating process allowed the microgels to diffuse across the entire substrate surface area for adsorption at the base and along the walls of the wells.…”
Section: Deposition Techniquesmentioning
confidence: 99%
“…Microgels are intramolecularly cross-linked micro/nanoscale polymeric colloids, whose network structure can be filled with free-flowing water. , Based on the advantage of colloidal stability, convenient preparation, facile functionalization, and good biocompatibility, microgels have evolved to be a good candidate as lubricating additives for hydration lubrication . In particular, stimuli-responsive microgels can be employed as smart lubricants for modulating the interfacial friction under the environmental stimuli (e.g., temperature, light, and pH). ,, As a representative, thermosensitive poly­( N -isopropylacrylamide) (PNIPAAm) based microgels have been widely studied for aqueous lubrication. , In 2013, Liu et al investigated the tribological behavior of poly­( N -isopropylacrylamide)- graft -poly­(ethylene glycol) (PNIPAAm- g -PEG) microgels and stated that these microgels exhibited a good lubricating effect between steel/steel contacts. In 2019, Xu et al further confirmed the aqueous lubricating performance of PNIPAAm microgels between steel and ultrahigh-molecular-weight polyethylene (UHMWPE).…”
Section: Introductionmentioning
confidence: 99%
“…22 In particular, stimuli-responsive microgels can be employed as smart lubricants for modulating the interfacial friction under the environmental stimuli (e.g., temperature, light, and pH). 20,23,24 As a representative, thermosensitive poly(Nisopropylacrylamide) (PNIPAAm) based microgels have been widely studied for aqueous lubrication. 25,26 In 2013, Liu et al 22 investigated the tribological behavior of poly(Nisopropylacrylamide)-graf t-poly(ethylene glycol) (PNIPAAmg-PEG) microgels and stated that these microgels exhibited a good lubricating effect between steel/steel contacts.…”
Section: ■ Introductionmentioning
confidence: 99%